2014
DOI: 10.1016/j.carj.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Tympanic Plate Fracture Frequency and Its Relationship to Mandibular Trauma

Abstract: The frequency of isolated tympanic plate fractures in maxillofacial trauma is low, but it is an important anatomic location. Condyle fractures are significantly associated with isolated tympanic plate fractures. The presence of these injuries should raise suspicion of a concomitant isolated tympanic plate fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Psimopoulou et al 15 and Chong and Fan 1 reported TPF following mandibular trauma. The studies conducted by Altay et al 17 and Wood et al 10 reported a similar prevalence of 58% of TPF following mandibular and temporal bone fractures. These studies also insinuate that the presence of condylar fracture should increase suspicion of TPF and be detected using high resolution CT of the temporal bone 10 17 .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Psimopoulou et al 15 and Chong and Fan 1 reported TPF following mandibular trauma. The studies conducted by Altay et al 17 and Wood et al 10 reported a similar prevalence of 58% of TPF following mandibular and temporal bone fractures. These studies also insinuate that the presence of condylar fracture should increase suspicion of TPF and be detected using high resolution CT of the temporal bone 10 17 .…”
Section: Discussionmentioning
confidence: 75%
“…The studies conducted by Altay et al 17 and Wood et al 10 reported a similar prevalence of 58% of TPF following mandibular and temporal bone fractures. These studies also insinuate that the presence of condylar fracture should increase suspicion of TPF and be detected using high resolution CT of the temporal bone 10 17 . Although TPF is usually associated with high intensity trauma, its relationship to low intensity trauma cannot be ruled out.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Tympanal bone fracture (TBF) is an uncommon complication of blunt head trauma and is mostly associated with a mandibular or petrous bone fracture [1][2][3][4][5][6][7][8][9][10]. It can lead to several complications, including external auditory canal (EAC) stenosis [2,5,11,12] with conductive hearing loss [8,11].…”
Section: Introductionmentioning
confidence: 99%